Age-dependent sympathetic neural responses to ß1 selective beta-blockade in untreated hypertension-related tachycardia - Dagmara Hering; Wiesława Kucharska; Marzena Chrostowska; Krzysztof Narkiewicz (Blood Pressure, 2018)
Background: Elevated heart rate (HR) increases cardiovascular morbidity and mortality in hypertension. The impact of beta-blockers on patient prognosis in hypertension is controversial. This study examined the age-related effects of betaxolol on HR, muscle sympathetic nerve activity (MSNA), blood pressure (BP) and sympathovagal balance in untreated males with hypertension and tachycardia. Methods: Ten young (age 26 ± 1 years) and seven older (age 50 ± 4 years) males underwent measurement of BP, HR, HR variability (Poincare plot) and MSNA before and after 8 weeks treatment with betaxolol at the initial starting dose of 10 mg/day, which was increased to 20 mg/day once daily after 4 weeks in all subjects. Results: In younger subjects, betaxolol decreased systolic BP (−13 ± 4 mm Hg, p = .01) and HR (−29 ± 4 bpm, p < .001) but not MSNA (3 ± 3 burst/min., p = 0.47) after 8 weeks. In older subjects a pronounced reduction in BP (−27 ± 7, p = .007) was accompanied by a significant decrease in MSNA (−13 ± 5 burst/min., p < .05) and HR (−17 ± 4 bpm, p = .002). SD1/SD2 ratio of Poincare plot increased in younger (0.36 ± 0.03 vs 0.51 ± 0.05, p = .004), but not in older (0.43 ± 0.08 vs 0.54 ± 0.12, p = .50) subjects. Conclusion: Autonomic neural responses to betaxolol are age-dependent in hypertension-related tachycardia. Betaxolol reduces sympathetic drive to the heart, but not to the peripheral vessels confirming the contribution of augmented cardiac sympathetic activity to disease pathophysiology in younger adults. In older hypertensives, the sympathovagal balance is not influenced by betaxolol. The paradoxical reduction in MSNA despite lowering of BP and HR in older patients may suggest age-related functional decrements in autonomic control and/or inhibitory effects of betaxolol on the central nervous system.